2020
DOI: 10.1021/acs.est.0c05621
|View full text |Cite
|
Sign up to set email alerts
|

The Twilight Zone as a Major Foraging Habitat and Mercury Source for the Great White Shark

Abstract: The twilight zone contains the largest biomass of the world’s ocean. Identifying its role in the trophic supply and contaminant exposure of marine megafauna constitutes a critical challenge in the context of global change. The white shark (Carcharodon carcharias) is a threatened species with some of the highest concentrations of neurotoxin methylmercury (MeHg) among marine top predators. Large white sharks migrate seasonally from coastal habitats, where they primarily forage on pinnipeds, to oceanic offshore h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 106 publications
2
28
0
Order By: Relevance
“…Rather than competition, overlapping regions of isotopic niches might therefore be due to some inherent approach limitations. For instance, stable isotopes have a poor ability to discriminate foraging depth for top-predators likely to feed in deep oceanic habitats (Choy et al, 2015;Kiszka et al, 2015) and only few studies have investigated the vertical dimension of resource partitioning in pelagic predator assemblages (Le Croizier et al, 2020b, 2020a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than competition, overlapping regions of isotopic niches might therefore be due to some inherent approach limitations. For instance, stable isotopes have a poor ability to discriminate foraging depth for top-predators likely to feed in deep oceanic habitats (Choy et al, 2015;Kiszka et al, 2015) and only few studies have investigated the vertical dimension of resource partitioning in pelagic predator assemblages (Le Croizier et al, 2020b, 2020a.…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly composed of fishes and invertebrates that are commonly targeted by marine megafauna (Aksnes et al, 2017;Davison et al, 2015;Hazen and Johnston, 2010). Among these predators, some pelagic shark species display typical deep diving patterns suggesting that they rely on this compartment, such as great white (Le Croizier et al, 2020a), blue (Braun et al, 2019) or scalloped hammerhead sharks (Jorgensen et al, 2009). Surprisingly, although the combined effect of climate change and fishing pressure is dramatically changing epipelagic fish biomass and dynamic (Pinsky et al, 2011;Tu et al, 2018), little attention has been paid to the mesopelagic zone which is also predicted to be affected by climate change (Proud et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Traveling-Midrange was more concentrated between the two main northern elephant seal colonies, and took place mainly at night and twilight hours. During night time, white sharks could take profit of the DSL rising from 350 to 500 m below to just a range of <200 m; in this sense, Becerril-García et al (2020) found squid tentacle fresh scars on the skin of white sharks from GuadalupeIsland, with strong evidence that these scars had appeared shortly since last observation; the access to these prey was also found byPapastamatiou et al (2020) with oceanic whitetip sharks, and LeCroizier et al (2020) confirmed the importance of mesopelagic prey contribution in Guadalupe's white shark diet. During dawn and sunset, this behavior possibly indicates a patrolling hunting strategy under low-light conditions, where the silhouette of the prey…”
mentioning
confidence: 88%
“…While the role of the island for this white shark population is unclear, evidence in previous studies showed that it can serve as a secondary nursery area for juveniles and as a feeding area for adults, which benefit from the pinniped colonies (mainly the northern elephant seal), although the frequency of attacks on them (seen at the surface) is not as high as in other areas such as California, which could be due to the excellent water clarity that allows ambush in deep waters (Domeier et al, 2012;Hoyos-Padilla et al, 2016;Skomal et al, 2015). Moreover, according to new evidence (Becerril-García et al, 2020;Le Croizier et al, 2020;Papastamatiou et al, 2020), Guadalupe Island could be more important than previously thought in terms of access to mesopelagic prey, acting as a barrier trap and hindering their dispersion.…”
Section: Unlike Many Other White Shark Aggregation Sites Guadalupementioning
confidence: 99%
“…It is unclear how white shark hunting strategies and predation might influence the population dynamics of the elephant seals in the GIBR. However, recent studies suggest that white sharks around Guadalupe Island include other important food items in their diet, such as large cephalopods and other deep-sea species (Becerril-García et al, 2020d;Le Croizier et al, 2020).…”
Section: Predator-prey Relationshipmentioning
confidence: 99%